Serum klotho is inversely associated with girth in older women but is not associated with falls or musculoskeletal measures in either sex - Bess Dawson-Hughes; Elsa M. Konieczynski; Lisa Ceglia (The Journal of Nutrition, Health and Aging)
Objective: Serum klotho, a biomarker of aging, has been associated with cardiovascular disease, kidney disease, and osteoarthritis, but information on an association with muscle and bone aging is limited. We assessed serum klotho as a potential biomarker of age-related changes in body composition, odds of falling, muscle strength and bone mineral density (BMD) in older adults. Design: Exploratory analysis within the STOP IT clinical trial. Setting: USDA Human Nutrition Research Center on Aging at Tufts University. Participants: Healthy adults (178 men; 209 women) age ≥65 years treated daily for 3 years with either 700 IU of vitamin D3 plus 500 mg of calcium or placebo. Methods: We examined associations of serum klotho (at 6 or 12 months) with odds of falling, and with baseline and 3-year changes in body composition, grip strength and spine and hip BMD by dual-energy X-ray absorptiometry (DXA). Results: Serum klotho levels did not differ significantly in the two treatment arms. In the arms combined, klotho was inversely associated with waist circumference (β= -0.007, p = 0.01) in the women but not in the men, after adjustment for age, physical activity, treatment assignment, kidney function, season and time of klotho measurement. Serum klotho was not associated with odds of falling or with proportion of body fat or lean mass, grip strength, or spine or hip BMD or their 3-year changes in men or women. Conclusion: Serum klotho is inversely related to waist circumference in healthy older women but not men. Serum klotho does not appear to be a useful biomarker of musculoskeletal status in older women or men.